CONFLICT RESOLVING MODEL KASI PEMERINTAHAN KELURAHAN KADEMANGAN (Studi pada optimalisasi penanganan dokumen kependudukan penduduk rentan di Kelurahan Kademangan) - Bambang Septiawan (Universitas Islam Balitar, 2019)
This research is focused to investigate the way of Vice Village Chief of Kademangan district which has responsibility in governmental affair to resolve conflict about the citizenship documentation of susceptible citizen. This research uses qualitative approach and concerns to fenomenologi area. The data is taken from unstructured interview and literature studies. The result show that conflict resolving model includes problem identification, consultation, meeting and constructing team, sosialiszation to the chief of neighborhood association, taking the data, processing data, separating the document, and evaluation as well as monitoring.